Inflammatory Markers as Predictors of Diabetic Nephropathy in Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Daniel-Corneliu Leucuța; Pauline Aurélia Fumeaux; Oana Almășan; Ștefan Lucian Popa; Abdulrahman Ismaiel (Medicina)
Background and Objectives: Diabetic nephropathy (DN) is a major complication of diabetes mellitus and a leading cause of end-stage renal disease. Inflammatory markers such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and red cell distribution width (RDW) have been proposed as potential predictors of DN progression. This study systematically reviews and meta-analyzes the role of these markers in DN. Materials and Methods: A comprehensive literature search was conducted to identify studies evaluating NLR, PLR, SII, and RDW in type 2 diabetes patients with normoalbuminuria, microalbuminuria, and macroalbuminuria. Five databases were searched: PubMed, Scopus, Embase, Web of Science, and LILACS. The Newcastle Ottawa Scale was used to assess the risk of bias in selected articles. Results: Out of 1556 records that were identified through searches, 40 were selected for the review. Finally, 35 were included for meta-analyses, including 13,519 patients. Higher levels of NLR, PLR, SII, and RDW were observed in macro- and microalbuminuria compared to normoalbuminuria, with significantly elevated NLR in microalbuminuria. Meta-analyses showed that NLR and RDW were significantly associated with higher odds of DN (NLR: OR 1.84, p < 0.001; RDW: OR 1.9, p = 0.023). However, PLR and SII were not significantly associated with DN. A longitudinal study confirmed SII as a significant predictor of DN progression (hazard ratio: 3.24, p = 0.023). Conclusions: This study highlights the potential of NLR and RDW as predictive markers for diabetic nephropathy.